PENGARUH REAL INTEREST RATE DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Moleong, Lysy Claudia (Modus Journals, 2018)
The objective of this study was to identify whethere there had been the influence of real interest rate toward financial distress and the influence of of leverage toward financial distress. In measuring the financial distress, the researcher made use of Z-Score Altman calculation model.Â  After measuring the financial distress, the researcher performed the logistic regression test in order to identify whether there had been the inter-variable influence. The population in the study was the manufacture companies that had been go public and that had been listed in the Indonesian Stock Exchange from 2004 until 2016. The results of the study showed that there had been significantly negative influence from the interest rate toward the financial distress and, on the other hand, there had been significantly positive influence from the leverage toward the financial distress. Â Keyword: Real Interest Rate, Leverage, Financial Distress, Logistic Regression.